RESPON WARGA BINAAN TERHADAP PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL OLEH DINAS KESEJAHTERAAN DAN SOSIAL PROVINSI SUMATERA UTARA DI DESA SIONOM HUDON SELATAN KECAMATAN PARLILITAN KABUPATEN HUMBANG HASUNDUTAN - Jane H Tampubolon (Welfare StatE, 2013)
Remoteness makes some communities in Indonesia still living in a very pathetic life. They stayed at the places that are geographically difficult to reach relatively. Remoteness makes them very limited to get basic social services, economic and political access. Education, health, and public utilities were something that are very rare to be felt by the community group. As citizens of the nation, they have not been able to involved on the development process and still continues lagging. They were introduced by the Ministry of Social Affairs as Traditional Remote Community. Traditional Remote Community is become one of the social welfare problem, so that the Indonesian government held an Empowerment Program for Traditional Remote Community which is expected to empower and improve the well-being of indigenous in various regions in Indonesia. The type of this research is descriptive research. The population in this research were all heads of households (families) who became inmates as many as 50 families. Analysis techniques using a single table that described in qualitative and quantitative analysis by using a Likert Scale to measure perceptions, attitudes and participation of inmates to Empowerment Program for Traditional Remote Community. Based on the analysis data, it was concluded that the Empowerment Program for Traditional Remote Community in Sionom Hudon Selatan was received a positive response with an average score is 0.38 that taken from the perception, attitude and participation of the community. The Empowerment Program for Traditional Remote Community is expected to be extended and further improvements, either in execution or socialitation, so that the community more participate and understand the intent and purpose of the Empowerment Program for Traditional Remote Community, take more benefits and positive impact for the welfare of the Traditional Remote Community in Indonesia. Key Words: Response, Empowerment, Traditional Remote Community